Strengthening Early Literacy Based on Local Culture: Design and Validation of The Interactive Multimedia “Si Leungli” for Early Childhood Education - Komara, Intan Budi; Murron, Faisal Sadam; Munawarti, Linda; Agustin, Intan Tri (International Conference on Elementary Education, 2025)
This study was driven by the limited availability of basic literacy teaching materials that integrate local cultural values for students in Phase A of elementary school. The research aims to develop and validate the interactive multimedia “Si Leungli” as a digital medium to strengthen basic literacy through West Javanese folklore. Using the Design and Development (D&D) approach with the PPE (Planning, Production, Evaluation) model, the study ensured a systematic and iterative process. In the planning stage, learning objectives were formulated according to the Merdeka Curriculum’s Phase A outcomes, focusing on early reading, basic writing, and text comprehension within a cultural context. The production stage produced an interactive audio-visual flipbook that includes folklore stories, engaging illustrations, and literacy activities such as reading, word guessing, writing, and coloring. In the evaluation stage, three categories of experts subject matter, learning, and media validated the product using a Likert-scale instrument, yielding a 94.8% feasibility score (excellent category). The results indicate that integrating folklore into interactive media enhances engagement, reading interest, and moral values like empathy, cooperation, and responsibility. The study contributes to culture-based emergent literacy theory and offers contextual, character-building learning innovations for early-grade teachers. In practice, this innovation can support Sustainable Development Goal (SDG) number 4 on Quality Education by promoting inclusive, equitable, and responsive early literacy learning.